Increased frequency of interleukin 2-responsive T cells specific for myelin basic protein and proteolipid protein in peripheral blood and cerebrospinal fluid of patients with multiple sclerosis - Zhang, J; Markovic-Plese, S; Lacet, B; Raus, J; Weiner, H L; Hafler, D A (The Journal of experimental medicine, 1994)
Equal numbers of CD4+ T cells recognizing myelin basic protein (MBP) and proteolipid protein (PLP) are found in the circulation of normal individuals and multiple sclerosis (MS) patients. We hypothesized that if myelin-reactive T cells are critical for the pathogenesis of MS, they would exist in a different state of activation as compared with myelin-reactive T cells cloned from the blood of normal individuals. This was investigated in a total of 62 subjects with definitive MS. While there were no differences in the frequencies of MBP- and PLP-reactive T cells after primary antigen stimulation, the frequency of MBP or PLP but not tetanus toxoid-reactive T cells generated after primary recombinant interleukin (rIL-2) stimulation was significantly higher in MS patients as compared with control individuals. Primary rIL-2-stimulated MBP-reactive T cell lines were CD4+ and recognized MBP epitopes 84-102 and 143-168 similar to MBP-reactive T cell lines generated with primary MBP stimulation. In the cerebrospinal fluid (CSF) of MS patients, MBP-reactive T cells generated with primary rIL-2 stimulation accounted for 7% of the IL-2-responsive cells, greater than 10-fold higher than paired blood samples, and these T cells also selectively recognized MBP peptides 84-102 and 143-168. In striking contrast, MBP-reactive T cells were not detected in CSF obtained from patients with other neurologic diseases. These results provide definitive in vitro evidence of an absolute difference in the activation state of myelin-reactive T cells in the central nervous system of patients with MS and provide evidence of a pathogenic role of autoreactive T cells in the disease.